2001
DOI: 10.1002/bies.1061
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral potential of chemokines

Abstract: In the past few years, a large number of new chemokines (chemotactic cytokines) and chemokine receptors have been discovered. The growth in knowledge about these molecules has been achieved largely through advances in bioinformatics and the expansion of expression sequence tag (EST) databases. It is now clear that chemokines are crucial in controlling both the development and functioning of leukocytes and that their role is not restricted to cell attraction, as originally assumed. In particular, recent finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…Given that chemokines are so crucial to the host immune response, it is not surprising that viruses have evolved several strategies to manipulate or interfere with chemokine function (23)(24)(25). Poxviruses express a family of secreted proteins collectively known as the T1͞35kDa CC-chemokine-binding proteins (CBPs) (26).…”
Section: T He Directed Migration Of Leukocytes Into Areas Of Inflammamentioning
confidence: 99%
“…Given that chemokines are so crucial to the host immune response, it is not surprising that viruses have evolved several strategies to manipulate or interfere with chemokine function (23)(24)(25). Poxviruses express a family of secreted proteins collectively known as the T1͞35kDa CC-chemokine-binding proteins (CBPs) (26).…”
Section: T He Directed Migration Of Leukocytes Into Areas Of Inflammamentioning
confidence: 99%
“…Some studies showed that chemokine receptors play crucial role in human immunodeficiency virus (HIV) infection [71]. Overall, the chemokines are important components of the endogenous host defense system [54,57].…”
Section: Introductionmentioning
confidence: 99%
“…Poxvirus vCkBP-I is able to bind a wide range of chemokines through binding the conserved glycosaminoglycan (GAG) binding domain. (10) By binding the chemokines in such a manner, it prevents them from binding the extracellular matrix, and therefore prevents the formation of a stable chemokine gradient (16,30) . Poxvirus vCkBP-I is also able to function in the first manner by direct neutralisation.…”
Section: Viral Chemokine-binding Proteins (Vckbp)mentioning
confidence: 99%
“…This vCk is able to act as a receptor antagonist for many CC and CXC receptors. (16) As such it is able to potently inhibit chemotaxis of neutrophils, macrophages and lymphocytes. This property may account for the conspicuous absence of inflammatory cells in MCV lesions, and the delayed or absent inflammatory response.…”
Section: Immune Evasion Through Modifying Chemotaxismentioning
confidence: 99%
See 1 more Smart Citation